Math, asked by mohammed3011abbas, 3 months ago

proof that (a-b-c)²=a²+b²+c²-2(ab-bc+ac)​

Answers

Answered by vaibhavrohilla1
29

Answer:

What is the formula for (a+b+c)²?

The formula is:

a2+b2+c2+2ab+2bc+2ca

PROOF:-

(a+b+c)2 can be written as (a+b+c)∗(a+b+c) ,

Therefore, (a+b+c)2=(a+b+c)∗(a+b+c)

=a(a+b+c)+b(a+b+c)+c(a+b+c)

=a2+ab+ca+ab+b2+bc+ca+bc+c2

=a2+b2+c2+ab+ab+bc+bc+ca+ca

=a2+b2+c2+2ab+2bc+2ca

Thanks for Reading!

Edit Credits: Lavjeet Singh

(a+b+c)²

Follow this, it might help.

There are three terms in the algebraic expression (a+b+c)

Square of the first term, plus square of the second, plus square of the third, plus twice the product of first and second, plus twice the product of second and third, and plus twice the product of third and first.

(a+b+c)² = a²+b²+c²+2ab+2bc+2ca = Σa²+2Σab

The are three square terms and three product terms. The square terms are always positive. For product terms, apply the product rule of signs.

(a-b-c)² = a²+b²+c²-2ab+2bc-2ca = a²+b²+c²+2(-ab+bc-ca)

(a-b+c)² = a²+b²+c²-2ab-2bc+2ca = a²+b²+c²+2(-ab-bc+ca)

(a

Hi,

You can get this formula by just simple multiplication method.

Lets proceed

(a+b+c) ^2

=(a+b+c)* (a+b+c) ;

=a*a + a*b + a*c + b*a + b*b + b*c + c*a + c*b + c*c;

=a^2 + ab + ac + ba + b^2 + bc + ca + cb + c^2;

=a^2 + b^2 +c^2 + ab +ba +bc +cb + ac + ca ;

=a^2 + b^2 + c^2 + 2ab + 2bc + 2ca;

So here we got the final result.

Therefore,

(a+b+c) ^2 = a^2 +b^2 + c^2 + 2ab + 2bc + 2ca.

plz make me brainlist

Answered by MrMonarque
64

Identity:-

  • \bold{(a-b-c)² = a²+b²+c²-2(ab-bc+ca)}

Proof:-

 {(a - b - c)}^{2}  \\ (a - b - c)(a - b - c)\\  {a}^{2}  - ba - ca - ab +  {b}^{2}  + bc - ca + bc +  {c}^{2}  \\  {a}^{2}  +  {b}^{2} +  {c}^{2}  - 2ab +    2bc - 2ca\\  \sf{a²+b²+c²-2(ab-bc+ca)}

\boxed{\tt{@MrMonarque}}

Hope It Helps You ✌️

Similar questions